The comparison of total Protein/Creatinine ratio versus 24-hour urine protein in women with suspected preeclampsia - E.Mobsheri (M.D); R.Azarhoush (M.D); H.Khoddam (M.Sc); MR.Rabeia (M.Sc); M.Tazik (M.D) (مجله دانشگاه علوم پزشکی گرگان, 2004)
Background & Objective: Preeclampsia is a common complications of pregnancy it’s about 5-7% in pregnants and it may complicate mother or fetus which ends with death. The purpose of this study was to determine the value of the protein/creatinine ratio in prediction of 24-hour urine total among women with suspected preeclampsia. Materials & Methods: 60 women who were evaluated for suspected preeclampsia at ?24 weeks of gestation were studied prospectively in Deziani Hospital Gorgan. There was no concurrent or preexisting systemic disease. They were undergoing a 24-hour urine collection for the determination of proteinuria. A single voided urine specimen was obtained after completion of the 24-hour urine collection and analyzed for the P/C ratio. Results: The random urinary protein to creatinine ratios is strongly associated with the 24-hour total protein excretion (P<0.05, R=0.75). The best cut off of 0.5 yields a sensitivity of 47% and a specificity of 100%. Conclusion: The random urinary protein to creatinine ratio could replace the 24-hour urine collection as a simple, faster more useful method for the diagnosis of significant proteinuria.